Pengaruh Fungsi Audit Internal terhadap Fee Audit pada Perusahaan Sektor Keuangan yang Terdaftar di BEI Tahun 2019-2022 - Pagiarri, Acasia Gieta; Afriyenti, Mayar (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the effect of the internal audit function on audit fees. This research is associative type with a quantitative approach. The population of this study were financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The sample was determined using purposive sampling technique and then resulted in 48 companies as samples. The statistical method used in this research is multiple regression analysis using the SPSS version 25 program. Audit fees as the dependent variable are measured by the natural logarithm of the audit fee. The internal audit function as an independent variable is measured by four measurements, namely the number of internal audit activities, internal audit size, internal audit certification, and frequency of internal audit meetings. This study is equipped with a control variable, namely company size. This study, through simultaneous testing results, shows that the independent variables jointly affect the dependent variable. However, partially, two of the four independent variable measurements, namely internal audit certification and frequency of internal audit meetings, have a positive and significant effect on audit fee payments. This research provides important implications for increasing the credibility of internal audit in the eyes of management and stakeholders.